2017
DOI: 10.1021/acsami.7b16036
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanotube-Doped Adhesive Films for Detecting Crack Propagation on Bonded Joints: A Deeper Understanding of Anomalous Behaviors

Abstract: A novel nanoreinforced adhesive film has been developed to detect adhesive deformation and crack propagation along the bonding line by means of the electrical response of the material. Adhesive films were doped by spraying an aqueous dispersion of carbon nanotubes (CNTs) over the surface. To determine the sensitivity of bonded joints, single lap shear (SLS) and mode-I fracture energy tests have been carried out while their electrical response has been measured. It has been found that CNT-doped adhesive films a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 45 publications
7
16
0
Order By: Relevance
“…This increase follows an approximately exponential behavior until failure, with the changes being more prevalent in the last stages of SLS testing. As stated in a previous study proving the monitoring capabilities of these CNT reinforced joints [28], the changes in the electrical resistance are due to the combination of two effects. The first effect was the increase of the tunneling distance between adjacent particles due to strain, leading to an increase of the tunneling resistance [52,53].…”
Section: Electrical Monitoringsupporting
confidence: 51%
See 2 more Smart Citations
“…This increase follows an approximately exponential behavior until failure, with the changes being more prevalent in the last stages of SLS testing. As stated in a previous study proving the monitoring capabilities of these CNT reinforced joints [28], the changes in the electrical resistance are due to the combination of two effects. The first effect was the increase of the tunneling distance between adjacent particles due to strain, leading to an increase of the tunneling resistance [52,53].…”
Section: Electrical Monitoringsupporting
confidence: 51%
“…The effect of CNT dispersion on the mechanical and electrical properties of carbon fiber reinforced plastic (CFRP) bonded joints in their initial state has been characterized in previous works [31]. It has been concluded that these CNT adhesive films do not induce a detrimental effect on mechanical performance and they have proved to have excellent monitoring capabilities by means of electrical measurements [28]. This work takes a further step by analyzing the potential and applicability of these proposed bonded joints under aging conditions.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…A previously published paper [25] details the adequate conditions to prepare a CNT-doped adhesive, as well as the resulting mechanical and electrical properties in a standardized single lap joint. The MWCNTs used for this study were NC7000, which were supplied by Nanocyl.…”
Section: Double Lap Cfrp Bonded Jointmentioning
confidence: 99%
“…Various non-destructive testing techniques, such as ultrasonic analysis, radiographic analysis, and IR-thermography, are adopted for structural health monitoring of materials [3] . A recently proposed in-situ health monitoring techniques is the damage analysis by electrical resistance measurement [4][5][6] . As depicted in the Figure 1.a-b, one can form an electrically conductive network in a non-conductive composite material by dispersing carbon nanotubes (CNTs) during the material manufacturing stage.…”
Section: Introductionmentioning
confidence: 99%